Balanced Matching and Labor Market Equilibrium - Burdett, Kenneth; Vishwanath, Tara (Journal of Political Economy, 1988)
We analyze equilibrium in a labor market model wherein it takes time for the workers to contact firms. Workers, assumed identical, repeatedly sell their labor services all through their work lives, choosing their search intensity endogenously. Identical firms attempt to maximize their steady-state profit flow. We focus on the importance and consequences of balanced matching, in which workers are more likely to contact a larger firm. A unique equilibrium is shown to exist wherein all firms offer the same wage and select an employment level at which wage equals marginal product. The effect of traditional labor market policies and empirical implications are discussed.